Determinants of regional development inequality in Sulawesi - Arif Budiman; Muhammad Yusri Zamhuri; Retno Fitrianti (Enrichment : Journal of Management, 2023)
This study was conducted to determine the level of development inequality (IW) in the province of Sulawesi and analyze how the effect of government transfer funds (DAU, DAK, and DBH) on regional development inequality in the province of Sulawesi. Data were collected from the provincial government budget realization reports for the period 2016 - 2021, totaling 6 provinces, using data on the official BPS website (www.bps.go.id), and the official website of each provincial government. The data were analyzed using the SPSS version 27 application in the form of multiple linear regression with a quantitative approach. The results showed that the average Williamson index in all Sulawesi provinces during the 2016-2021 period was 0.509561, which means that there was quite high development inequality, further analysis showed that general allocation funds (DAU) and revenue sharing funds (DBH) had a positive and significant effect on development inequality (IW).